2017
DOI: 10.2215/cjn.11411116
|View full text |Cite
|
Sign up to set email alerts
|

National Healthcare Safety Network (NHSN) Dialysis Event Surveillance Report for 2014

Abstract: The 2014 National Healthcare Safety Network Dialysis Event data represent nearly all United States outpatient dialysis facilities. Rates of infection and other dialysis events were highest among patients with a central venous catheter compared with other vascular access types. Surveillance data can help define the epidemiology of important infections in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
141
8
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(162 citation statements)
references
References 25 publications
11
141
8
2
Order By: Relevance
“…In this study, the overall pooled three events rate was 1.60 per 100 patient‐months. The rate was slightly higher than 1.47 per 100 patient‐months from an earlier study based on tertiary hospitals in China, but it was lower than the figures from previous studies in the United States (4.75 per 100 patient‐months) and Saudi Arabia (3.1 per 100 patient‐months) . Two important issues should be noted when results of this study were compared with studies from other countries.…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations
“…In this study, the overall pooled three events rate was 1.60 per 100 patient‐months. The rate was slightly higher than 1.47 per 100 patient‐months from an earlier study based on tertiary hospitals in China, but it was lower than the figures from previous studies in the United States (4.75 per 100 patient‐months) and Saudi Arabia (3.1 per 100 patient‐months) . Two important issues should be noted when results of this study were compared with studies from other countries.…”
Section: Discussioncontrasting
confidence: 70%
“…Two important issues should be noted when results of this study were compared with studies from other countries. First, the utilization of fistula was much higher in present study (85.3%) than that in studies from the United States (62.8%) and Saudi Arabia (57.7%), as it has been reported that fistula was associated with decreased infections and complications. Second, although oral antimicrobial start was not a dialysis event of NHSN, however, dialysis patients in China often use oral antimicrobial agents with/without prescriptions to treat infections, rather than IV antimicrobial agents .…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…However, these efforts have not translated into sustained improvement at the operational level. Legislated infection control measures, like the National Healthcare Safety Network, have created controversy about facility under-reporting and data integrity, obfuscating discussion about the real goal of a large-scale, systematic, and process-driven infection control program in the United States to support local and regional efforts (25,26).…”
Section: The Importance Of Strategic Leadership and Alignmentmentioning
confidence: 99%